Upaya Kepala Taman Pendidikan Alquran (TPA) Masjid Mustaqim Batusangkar dalam Menanamkan Karakter Disiplin Santri dan Santriwati - Ratmiati, Ratmiati; Muspardi, Muspardi; Febrian, Vicky Rizki; Setiawan, Eko Muda; Yusmanila, Yusmanila (UIN Mahmud Yunus Batusangkar, 2024)
This research aims to describe (1) The disciplinary conditions of female students at the TPA, (2) The efforts of the head of the TPA to instill a disciplinary character in the students. This research is descriptive qualitative research. The subjects of this research were school principals, teachers and students at the Mustaqim Mosque Batusangkar TPA. The data collection techniques used were observation, interviews and documentation. The data analysis technique used is the theory of Miles and Huberman which is carried out by (1) Data reduction (2) Data presentation (3) Drawing conclusions and verifying. Checking the validity of the data was carried out by extending observations and triangulation. The triangulation used in this research is source triangulation which is carried out by checking data that has been obtained through several sources. The results of research conducted by researchers show that (1) Students lack discipline in carrying out rules, students often make noise during lessons, there are students who disturb their friends while studying, students who go in and out of local areas during lessons without the teacher's permission, students who go to toilets without the teacher's permission, and students who deny the teacher's orders, and students who often criticize their fellow students. (2) The efforts of the head of the TPA as a leader in the school are in the form of (a) Providing continuous coaching in terms of modeling, (b) Teaching, and (c) Strengthening the good character of teachers. and TPA students. Keywords: headmaster, Santri, TPA, Disciplinary Character